Reassessing the 'gift relationship': the meaning and ethics of blood donation for genetic research in the UK - Busby, Helen Wynne (2004)
This thesis is based on a critical re-appraisal of Richard Titmuss' classic formulation of gift relationships, which has long been a point of reference for thinking about blood donation in Britain. It argues that Titmuss' interest in the intersections of social systems and health care, together with his concern with mutuality, has been lost in the characterisation of blood donation as a uniquely altruistic activity. This argument is applied to some key assumptions about blood donation in Britain in the thesis, which considers their historical and political contours, and interrogates them in the light of the development of large biobanks which require blood samples for genetic research.